Nature Narratives in Serat Palilindon 9 L 197: Cheryll Glotfelty Ecocritical Studies - Iftitah Ulfiana Maghribi; Yosi Wulandari; Ghis Nggar Dwiadmojo (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Serat Palilindon 9 L 197 is a palm-leaf manuscript written in the Buda script from the Merapi-Merbabu tradition that records narratives of disasters, especially earthquakes (lindu), as cosmic events laden with moral, social, and spiritual meaning. This manuscript reflects the worldview of pre-modern Javanese society, which interpreted nature not merely as a physical phenomenon, but as the language of the cosmos and a means of ecological ethics. This study aims to analyze the representation of nature in the Palilindon section (lempir 2r-4v) through Cheryll Glotfelty's ecocritical approach using the concepts of nature as text, environmental ethics, and human-nature interaction. The research uses a descriptive qualitative method with content analysis techniques (Krippendorff, 2018). The main data consists of digital manuscripts from the National Library of Indonesia (Khastara) collection and validated transliteration results. The results of the study show five thematic categories, namely (1) natural phenomena as signs of disharmony, (2) human socio-spiritual responses to disasters, (3) symbolic/cosmological meanings through the Hijri calendar, (4) the reciprocal relationship between humans and nature, and (5) ecological values that emphasize solidarity and cosmic balance. The conclusion of the study affirms that Serat Palilindon presents nature as an active agent and an ethical, spiritual text that teaches balance among faith, morality, and ecology.